IL-10 Gene-Modified Human Amniotic Mesenchymal Stem Cells Augment Regenerative Wound Healing by Multiple Synergistic Effects - Xiao, Shune (Stem Cells Int, 2019)
Mesenchymal stem cells (MSCs) possess a capacity to enhance cutaneous wound healing that is well characterized. However, the therapeutic effect of MSCs appears to be limited. Modifying MSC target genes to increase necessary biological effects is a promising strategy for wound therapy. Interleukin-10 (IL-10) is an anti-inflammatory cytokine that has a therapeutic effect on wound healing. In this study, we modified human amniotic mesenchymal stem cells (hAMSCs) using recombinant lentiviral vectors for expressing IL-10 and evaluated the therapeutic effects of hAMSCs-IL-10 in wound healing. We elucidated the mechanisms underlying the effects. We found that promoting wound healing was maintained by synergistic effects of hAMSCs and IL-10. hAMSCs-IL-10 showed stronger biological effects in accelerating wound closure, enhancing angiogenesis, modulating inflammation, and regulating extracellular matrix remodeling than hAMSCs. hAMSCs-IL-10 would be better at promoting wound healing and improving healing quality. These data may provide a theoretical foundation for clinical administration of hAMSCs-IL-10 in cutaneous wound healing and skin regeneration.